Identification of a novel alpha1-antitrypsin variant. (2017) - de Seynes, Camille; Ged, C.; de Verneuil, H.; Chollet, N.; Balduyck, M.; Raherison, C.
Abstract: Alpha-1-antitrypsin deficiency (A1ATD) is a genetic condition caused by SERPINA1 mutations, which results into decreased protease inhibitor activity in the serum and predisposes to emphysema and/or to liver disease due to accumulation of the abnormal protein in the hepatic cells. In most cases the clinical manifestations of A1ATD are associated with PIZZ (p.Glu366Lys; p.Glu366Lys (p.Glu342Lys; p.Glu342Lys)) or PISZ (p.Glu288Val; p.Glu366Lys (p.Glu264Val; p.Glu342Lys)) genotype, less frequently, deficient or null alleles may be present in compound heterozygous or homozygous A1AT deficient patients. We report the identification of a novel alpha1-antitrypsin variant in a 64-year old woman presenting with dyspnea on exertion. Imaging revealed bilateral bronchiectasis associated with moderate panacinar emphysema. The pulmonary function tests (PFTs) were subnormal but hypoxemia was noticed and A1AT quantitative analysis revealed a severe deficiency. DNA sequencing showed compound heterozygosity for the PIZ variant and a novel missense variant p.Phe232Leu (p.Phe208Leu). No specific treatment was proposed since PFTs were within the normal range at this stage of the disease. Close follow-up of pulmonary and hepatic parameters was recommended.